2022
DOI: 10.1039/d2nj02361j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of NiCo-X (X = OH, S, Se, P) nanodiscs and comparison of their electrocatalytic performances in an electrochemical sensing platform

Abstract: In this paper, the NiCo-X (X= OH, S, P, Se) nanodiscs (NDs) were synthesized. Firstly, the nickel-cobalt hydroxide (NiCo-OH) precursors with the nanodisc-like structure were prepared by a hydrothermal method....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…The critical processes during the construction of sensors with high sensitivity and high selectivity are the enhancement of the charge transfer rate on the electrode surface and the specific recognition of the target molecules. 9,10 It has been reported that chemical modification of the bare electrode using functional materials is an effective method of changing the microstructure of the interface between the electrode and the electrolyte and can significantly improve the redox properties of the electrode and the sensing performance toward specific target molecules. 11,12 Hence it is efficient to improve the selectivity and sensitivity of sensors via the functional modification of electrode surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The critical processes during the construction of sensors with high sensitivity and high selectivity are the enhancement of the charge transfer rate on the electrode surface and the specific recognition of the target molecules. 9,10 It has been reported that chemical modification of the bare electrode using functional materials is an effective method of changing the microstructure of the interface between the electrode and the electrolyte and can significantly improve the redox properties of the electrode and the sensing performance toward specific target molecules. 11,12 Hence it is efficient to improve the selectivity and sensitivity of sensors via the functional modification of electrode surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterial-modified transducer interfaces enhance biomolecule enrichment due to their high surface area, leading to highly sensitive detection. Herein, we hypothesize that integrating semiconductor quantum dots (QDs) superlattices with MIPs can offer unique transducer functionality for the development of highly sensitive and reliable ratiometric electrochemical nanosensors for SARS-CoV-2. QDs are zero-dimensional metal chalcogenides with particle sizes smaller than their excitonic Bohr radius, exhibiting unique optical and electronic properties due to quantum mechanical effects.…”
Section: Introductionmentioning
confidence: 99%